DESVENDANDO AS PRÁTICAS AVALIATIVAS DE PROFESSORES DE MATEMÁTICA EM TURMAS DO 1º ANO DO ENSINO MÉDIO DA CIDADE DE GOIÂNIA - CUNHA, Maria Francisca da (2009)
This study aimed to examine how to develop assessment practices in mathematics classes in the first year of high school in seven Colleges of Goiânia. Authors such as Luckesi, Moretto, Buriasco, Valente, among others, formed the theoretical framework for analysis. Data collection was conducted through a questionnaire to 183 students and 7 graduate teachers in mathematics and through semi-structured only to teachers. The main points, which was highlighted in the questionnaires and interviews, served as a contribution to define the analysis by categories. These categories helped us to understand how assessment practices were carried out by teachers and how they were viewed by their students. From the analysis undertaken it is clear that in all colleges, as expected, the essay question exam is the most used as a form of assessment. However, we emphasize that the student's participation is increasingly being considered in the evaluation in the following forms: observation of participation, group work, monitoring reports of overall performance, tests and exams in pairs with consultation. Another key note is that teachers who use most forms of monitoring of student performance are precisely those with a low weekly workload of conducting with exclusive hours to devote to these activities.